PARTISIPASI MASYARAKAT DALAM PENANGANAN PROGRAM PANGAN (STUDI SAAT MENGHADAPI COVID 19 DI KAMPUNG INTAAP DISTRIK RANSIKI KABUPATEN MANOKWARI SELATAN PROVINSI PAPUA BARAT) - Saroy, Tobias; Goni, Shirley Y. V. I.; Zakarias, Jhon D. (HOLISTIK, Journal Of Social and Culture, 2021)
Management of food programs, where the government still prioritizes the handling of food programs as an alternative to overcome the dangers of the population from hunger. Each region usually has a difference in managing food programs because food management in each region is not always uniform. Food program di Intaap village is still one of the mainstay programs of the farming community, so to be able to survive during theCovid-19 pandemic in farmers must be more active in trying. In the end, this pandemic not only threatens safety, public health, but also terrorizes the food sector, ranging from production, distribution, to consumption.That in handling the Food program when facing the crisis during the Covid 19 period, various strategies are needed to maintain the needs of the community. Therefore, the government has tried and taken steps in handling food security, so that the strategy prepared by the intaap village government through several programs that have been prepared, among others, through the assistance of agricultural production facilities to the intaap villagers.Community participation in the handling of food programs is very important, especially in the village of Intaap Ransiki District, South Manokwari Regency. Forms of community participation in the handling of food programs in accordance with the results of research, among others in the form of labor participation. Such energy participation can be seen in their participation to support the success of the Food program.Â Keywords: food, participation, strategy